Urban economic consideration and land use affecting its growth and government’s legislation / Samsol Bahri Jamari and Rahmat Salim - Jamari, Samsol Bahri; Salim, Rahmat (Faculty of Architecture, Planning and Surveying, 1986)
The purpose of this disertation is to study the development of the urban economic as a new field of economic which has paralelled increased interest in domestic urban-problems. The development of this urban economics affected the land use pattern and the property market operation and the government legislation in term of planning policy as in general and other policies which is related and the view of the public, private and other agencies towards the urban design development. The study of this aspect would cover the area of Kuala Lumpur city core which act as a basis of this study and the development of urbanization at present is beyond control and a lot of negative issues created in the urban design proper.